Non-communicable diseases among children in Ghana: health and social concerns of parent/caregivers - Anarfi, J.K.; Yawson, A.E.; Abuosi, A.A.; Badasu, D.M.; Atobra, D.; Adzei, F.A. (My University, 2016)
Background: Globally, there is a progressive rise in the burden of non-communicable diseases (NCDs). This paper examined the health and social concerns of parents/caregivers on in-patient care for children with NCDs in Ghana. Methods: This was a cross-sectional study in three large health facilities in Ghana (the largest in the South, the largest in the North and the largest in the Eastern part of Ghana. Data was collected with a structured questionnaire among 225 caregivers (≥18 years) of 149 children with NCDs in health facilities in the three regions. Data was analyzed with simple descriptive statistics. Results: Most caregivers 169(75.0%) were women, relatively young (median age 35years), mostly married and resided in urban areas. Sickle cell disease was the commonest NCD among the children. All 169(75.0%) caregivers believed children suffer NCDs because of sins of parents/ancestors, 29(12.9%) believed herbalists/spiritualists have insights into treating NCDs and 73(32.6%) have previously used herbs/traditional medicine for child's illness. NCD in children was a burden and caused financial difficulties for families. Most caregivers (>96.0%) indicated NCDs in children should be included in national health insurance benefits package and a comprehensive national NCD policy is needed. Conclusion: Absence of national NCD policy for children is a major challenge. The burden of care rests mainly on the parents/caregivers. A national strategic intervention on the importance of awareness generation on the causes, risk factors, prevention and treatment of NCDs for families and communities is essential. Government support through national health and social policy initiatives are essential.
Keywords: Ghana; Non-communicable; diseases